Redefining (interior)scapes: integrating the natural and built environment - Fakhraldeen, Sukaina (Kansas State University, 2012)
In the temperate Midwest, interiorscapes are seldom a feature of public schools. The interior spaces of school environments tend to be dull, uninspiring, and do very little to nurture the wellbeing and needs of students. Interiorscapes can greatly influence the overall productivity of users by creating healthy, pleasant environments. Schools fail to create richer indoor environments for a number of reasons, such as lack of resources as well as knowledge about the design, implementation and benefits of interiorscapes. In addition students today “are not the outdoor-living [children] they were 100 years ago, and as much as 90% of [their] time may be spent indoors” (Manaker, 2). Healthy and stimulating school environments have the potential to enhance students’ productivity and creativity. Therefore the question at hand is: how can a Manhattan Kansas’ high school integrate the natural and built environment to create richer interior spaces? In this Master’s report, I explore the potential benefits of designing an interiorscape that integrates the natural and built environments within a school setting. Using Manhattan High School West Campus as the project site, I analyzed the effect and design of existing interiors on students through passive observation. Numerous research precedents identified valuable information on design processes and methodologies for designing interiorscapes and evaluating user interaction with existing places. Following a thorough analysis of the typology and characteristics of each precedent, I considered unique facets that were directly applicable to my project site. I then went to test the aspects selected from these precedents by incorporating them into the design for the selected project site; north courtyard and adjacent interior dining space. Based upon the precedent research and literature review, design goals and objectives evolved. The end product is a schematic design for Manhattan’s High School cafeteria area and north courtyard. The plan encompasses desired characteristics of an interiorscape and needs of its potential users. Ultimately, this proposal presents ideas for ways of implementing interiorscapes to enhance the overall productivity of users, while simultaneously strengthening the relationship between the natural and built environments.
Keywords: Landscapes of Learning; Interiorscapes; People-plant relationships; Controlled environment; integration; Landscape Architecture (0390)